Os gestos na interação de crianças ouvintes e surdas: as possibilidades de um contexto bilíngue. - Ferreira, Waléria de Melo (2010)
This research regards an observational, qualitative study, which involves 08 (eight) hearing children and 03 (three) deaf children, aged between 7;7 and 11;10, in spontaneous daily interactions within a 3rd year Elementary School classroom in an inclusive private school, in Arapiraca, Alagoas. Our main goal is to identify the strategies adopted by hearing children for effective communication between them and the deaf. The corpus consists basically of 08 (eight) video recordings, each including 08 (eight) 30 minute sessions, from which we selected 09 (nine) episodes for analysis. We based our research on Kinesics, Proxemics and Tacesics, as well as on some studies on gesture in the acquisition and development of oral language and in the acquisition of sign language, based on Interactional Linguistics. Our thesis is that children have the ability to adapt linguistically to their interlocutors and our main hypothesis is that when interacting with deaf children, hearing children produce gestural speech that allow them to confirm, deny, ask, describe, narrate, explain, etc. and they are developing a communicative competence in a second language Brazilian Sign Language - to the point of being able to switch between the oral and sign language in an attempt to adapt their speech to the deaf children. Our analyses confirm our thesis that the children observed have the ability to adapt linguistically to their interlocutors, and show that sign language development occurs on a gesture-to-sign continuum, where the gestures socially learned and shared by both hearing and deaf children, enable the construction of meaning and, therefore, the achievement of communication between them.